Meningkatkan Minat Membaca Al-Qur’an Pada Siswa SDN I Waindawula - Usman Usman; Asti Sulistia; Nur Indah Haris; Siti Fatimah (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
This journal discusses increasing in reading the Qur’an. In order to increase student’s interest in learning to read the Al-Qur’an, the role of Islamic Religious Education teachers is needed. Because students, especially at the elementary school level, still really need guidance in reading the Qur’an. Forms of efforts to increase increase interest in learning to read the Qur’an are advising through words, praying for students, praise as motivation, sincereaffection, educating by example, not exaggerating in advising, gradual habituation. The inhibiting factor for increasing interest in learning to read the Qur’an are family factors including the way parents educater their children, relations between family members and the household atmosphere, environmental factors of uneducated people, as well as school environmental factors, especially peer association. While the supporting factors are dividied into several parts, namely physica factors including health and disabilities, psychological factor inculiding intelligence, attention, interests, and talents, and fatigue factors physical and spiritual fatigue including.